Comparison Of Three Diagnostic Methods For Detecting Rabies Virus In Animals - Chandrashekhara, N.; Rathnamma, D.; Isloor, S.; Yathiraj, S.; Sathyanarayana, M.L.; Veeresh, B.H.; Rao, Suguna; gowda , B.M. Veere (Indian Journal of Veterinary Sciences and Biotechnology, 2013)
In the present study three diagnostic methods viz., Fluorescent antibody test (FAT), Direct Rapid Immunohistochemistry Test (DRIT) and Reverse Transcriptase Polymerase Chain Reaction (RT PCR) were evaluated to diagnose rabies. A total of 30 brain samples of rabies suspected animals were received for postmortem (including dogs (n=20), cattle (n=08) and cats (n=02) from different geographical locations in Karnataka). Out of the 30 animal brain samples tested, 22 (73.3%) were positive for rabies according to the FAT. The sensitivities and specificities of DRIT and RT-PCR were 100% equivalent with FAT. The DRIT appears to be a fast and reliable assay that can be used to analyze brain samples. The results indicated that DRIT and RT- PCR can be used as supplementary diagnostic tools for detecting rabies viruses in field and laboratory conditions respectively.